Enhancing photoelectrochemical hydrogen production over Cu and Ni doped titania thin film: Effect of calcination duration - Bashiri, R. (Elsevier Ltd, 2017)
In this study, Cu-Ni/TiO2 photocatalyst was synthesized using sol-gel coupled with hydrothermal followed by calcination. The effect of variation in calcination durations (60, 90, and 120 min) on solar hydrogen production was studied over Cu-Ni/TiO2 photocatalyst in a photoelectrochemical (PEC) cell, connecting to a dye sensitized solar cell (DSSC) in series. The various techniques used for characterization of physicochemical and photoelectrochemical properties of photocatalysts. The 120 min calcined photocatalyst was the most effective photocatalyst with total produced hydrogen of 376.4 μmol/cm2 compared to others. The physicochemical studies revealed that a better photocatalytic performance of 120 min calcined photocatalytic attributed to its high crystallinity, more absorbance in the visible region, reduction of grain boundaries, less bulk trapping center and surface state, and high Cu+:Cu2+ ratio on the surface of the photocatalyst. This enhanced physicochemical properties reduced charge transfer resistance and increased the electron lifetime and photocurrent density as confirmed by electrochemical impedance spectroscopy (EIS) analysis. Furthermore, Mott-Schottky (M-S) analysis showed that the increase in calcination duration improved the flat band potential which facilitated efficient charge separation at the electrode/electrolyte interface with large carrier densities. © 2017 Elsevier Ltd.